STRATEGI BADAN PENDAPATAN DAERAH DALAM MENINGKATKAN PENERIMAAN PAJAK KENDARAAN BERMOTOR DI PROVINSI SULAWESI UTARA - Erick Evans Maabuat; Sutiyo Sutiyo; Layla Kurniawati (Institut Pemerintahan Dalam Negeri, 2022)
As a manifestation of the implementation of regional autonomy, the duties and authorities to regulate and manage the government and interests of the local community are left to the local government itself. This task is carried out while still being guided by the legislation, namely Law No. 23 of 2014 concerning Regional Government. Decentralization aims to make local government more efficient and effective. The Regional Autonomy System signals that a government prioritizes regional independence to regulate its own government affairs. The implementation of autonomy, one of the goals of which is to accelerate the service process in the community. Fiscal decentralization in the context of autonomy has become the basis of regional sources of revenue. In this case, local governments are given the right to obtain financial resources in the form of certainty of the availability of funding from the government according to the government affairs submitted. The government is given the authority to collect and utilize local taxes and levies, the right to obtain proceeds from national resources located in the regions and other balances as well as to manage regional wealth and obtain sources of financing (Soleh and Heru, 2010). The purpose of this study is to formulate and analyze how much potential Motor Vehicle Tax is and the impact of the Tax on Local Revenue (PAD) and then formulate the right strategy in answering problems in an effort to increase the realization of motor vehicle tax John W. Creswell (2019: 288) stated that,